Gold Prices Movements and Predictions with Reference to Indian Context - Pol, Naveen; Poddar, Arindam; Thomas, Feba (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the research is to forecast the gold price (IND), with the assistance of traditional method of Time Series, for example Box –ARIMA model, which gives us better outcomes for decision making, and furthermore helps the investors in forecasting the effectiveness of savings in the Gold Market. During this investigation the data of gold price from 2014 to 2019 have taken for examining the influence for predicting of gold price based on Time Series ARIMA (p,d,q) model. Forecasting is a capacity in the executives to help decision making. It is additionally described as the procedure of estimate in unknown future situations. In an increasingly broad term it is normally known as prediction which refers to estimation of time series or longitudinal type data. Gold is a valuable yellow product which can be convert into cash at any time. Time series ARIMA is the best technique for forecasting, modeling and characterization, all of which have been utilized in this investigation. For optimum accuracy Auto Correlation and Partial Correlation analysis have been utilized as a statistical support, and simultaneously. The rate of gold is keep on rising every day. So, by predicting the price of gold an individual can buy and invest his money on gold according to his suitability. The ARIMA model helps in finding the cost of gold in coming year. Research implication: people who are trading in different market share and people who are in the field of buying and selling of gold are also going to be benefited by this research. The findings of through ANIMA model the movement of gold price for coming next 5 years is predicted.